Difteria: doença reemergente - Rodrigues Silva, Marcela; L. Liphaus, Bernadete; Marques Ferreira, Patricia Marques Ferreira; Frugis Yu, Ana Lúcia; R.M.P. Carvalhanas, Telma (BEPA. Boletim Epidemiológico Paulista, 2019)
.